Mongolian horses past and present: What do we know and where do we go? - Conte, Cecilia (Acta Mongolica, 2025)
The introduction of domestic horses and riding during the 2nd millennium BC triggered profound changes in prehistoric Mongolian societies. The connection between horses and humans was instrumental for the creation of past nomadic states. Until today, horses remain beloved animals which play a major role in subsistence, ritual as well as national narratives. Horses, with their special economic and symbolic place in both Mongolia’s ancient past and its present, have been largely studied from either an archaeological or an anthropological point of view. This paper simply asks: what do we know about Mongolian horses, past and present, and where do we go from here? It provides an overview of recent archaeological and anthropological debates concerning horses in Mongolia with a focus on the Bronze Age and present, respectively, and explores the potential for future interdisciplinary studies. Amongst the variety of subjects discussed here are Mongolia’s khirigsuur burial mound complexes; recent genetic advances regarding horse domestication; and contemporary multi-species herding practices, material culture, and concepts. Based on this extensive review of horse-related literature and the author’s own archaeological and ethnographic research in Mongolia, established scientific dichotomies such as wild vs. domesticated and human vs. non-human will be re-evaluated in favour of more relational approaches.